The Role of ASEAN through ASEAN Integrated Food Security Framework (AIFS) in Achieving Indonesia’s Food Security - Miryanti, Renny; Wijayanti, Sri; Saadah, Kholifatus; Agustiningsih, Ayu (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural DevelopmentDO - 10.20884/2.procicma.2023.2.1.7815, 2023)
The report of 2021 hunger map of the World Food Program of the United Nations (WFP) shows that even though Southeast Asia has fertile land and is surrounded by maritime wealth, however many ASEAN (Association of Southeast Asian Nations) countries still has a number of poverty and inability to access food and nutrition. ASEAN through the AIFS (ASEAN Integrated Food Security) Framework encourages ASEAN countries try to achieve ASEAN regional food security. This study will examine the role of ASEAN through AIFS (ASEAN Integrated Food Security) in achieving Indonesia’s food security. This research used qualitative method, and the collecting data used primary data collection conducted through interviews with related parties, and secondary data through literatures review related to the role of ASEAN through ASEAN Integrated Food Security Framework or other food security policies. The theory of international organization role is used to answer the research question. This research found that ASEAN through AIFS framework plays role as an arena rather than instrument and independent actor in achieving food security in Indonesia.